Answer:
14/3
Step-by-step explanation:
Simplify the following:
48/6 - 10/3
Hint: | Reduce 48/6 to lowest terms. Start by finding the GCD of 48 and 6.
The gcd of 48 and 6 is 6, so 48/6 = (6×8)/(6×1) = 6/6×8 = 8:
8 - 10/3
Hint: | Put the fractions in 8 - 10/3 over a common denominator.
Put 8 - 10/3 over the common denominator 3. 8 - 10/3 = (3×8)/3 - 10/3:
(3×8)/3 - 10/3
Hint: | Multiply 3 and 8 together.
3×8 = 24:
24/3 - 10/3
Hint: | Subtract the fractions over a common denominator to a single fraction.
24/3 - 10/3 = (24 - 10)/3:
(24 - 10)/3
Hint: | Subtract 10 from 24.
| 2 | 4
- | 1 | 0
| 1 | 4:
Answer: 14/3
Answer:
i think c
Step-by-step explanation:
Answer:
1 + ln 2 - ln x
Step-by-step explanation:
ln ( 2e /x)
We know that ln ( a/b) = ln ( a) - ln (b)
ln (2e) - ln (x)
We also know that ln ( a*b) = ln a + ln b
ln ( 2) + ln e - ln x
We know that the ln e = 1
ln 2 + 1 - ln x
Changing the order
1 + ln 2 - ln x
Answer:
579o
Step-by-step explanation:
61+ 62=123o
180-123= 57
J = 57o